Added-value of ancillary imaging features for differentiating hepatocellular carcinoma from intrahepatic mass-forming cholangiocarcinoma on Gd-BOPTA-enhanced MRI in LI-RADS M. - Zheng, Wanjing; Huang, Hongjie; She, Dejun; Xiong, Meilian; Chen, Xiaodan; Lin, Xiaojun; Cao, Dairong (Abdominal Radiology, 2022)
Objective: To identify the reliable imaging features and added-value of ancillary imaging features for differentiating hepatocellular carcinoma (HCC) and intrahepatic mass-forming cholangiocarcinoma (IMCC) assigned to LI-RADS M on Gd-BOPTA-enhanced MRI. Methods: This retrospective study included 116 liver observations assigned to LI-RADS M, including 82 HCC and 34 IMCC histologically confirmed. Before and after adding ancillary imaging features, all variables with a p-value of < 0.05 in univariable analysis were entered into a multivariable logistic regression analysis to build diagnostic model 1 and model 2 to find reliable predictors of HCC diagnosis. Receiver operating characteristic (ROC) analysis and the DeLong test were used to compare the two models. Results: Forty-nine of 82(59.8%) HCCs had a considerably higher frequency of enhancing "capsule" compared with IMCCs (p < 0.001). Based on LI-RADS major and LR-M features and clinical-pathologic factors, an elevated AFP level (OR = 10.676, 95%CI = 2.125–4.470, p = 0.004) and enhancing "capsule" (OR = 20.558, 95%CI = 4.470–94.550, p < 0.001) were extracted as independent risk factors in Model 1. After adding ancillary imaging features, Male (OR = 23.452, 95%CI = 1.465–375.404, p = 0.026), enhancing "capsule" (OR = 13.161, 95%CI = 1.725–100.400, p = 0.013), septum (OR = 17.983, 95%CI = 1.049–308.181, p = 0.046), small-scale central HBP hyperintensity (OR = 44.386, 95%CI = 1.610–1223.484, p = 0.025) were confirmed as independent significant variables associated with HCC. Model 2 demonstrated significantly superior AUC (0.918 vs 0.845, p = 0.021) compared with Model 1. When any two or more predictors in model 2 were satisfied, sensitivity was 91.46%, and accuracy was at the top (87.93%). Conclusion: Enhancing "capsule" was a reliable imaging feature to help identify HCC. Adding ancillary imaging features improved sensitivity and accuracy for HCC diagnosis with differentiation from IMCC in LR-M.